The unique structural and functional features of CXCL12. Issue 4 (April 2018) - Janssens, Rik; Struyf, Sofie; Proost, Paul
Abstract The CXC chemokine CXCL12 is an important factor in physiological and pathological processes, including embryogenesis, hematopoiesis, angiogenesis and inflammation, because it activates and/or induces migration of hematopoietic progenitor and stem cells, endothelial cells and most leukocytes. Therefore, CXCL12 activity is tightly regulated at multiple levels. CXCL12 has the unique property of existing in six splice variants in humans, each having a specific tissue distribution andin vivo activity. Controlled splice variant transcription and mRNA stability determine the CXCL12 expression profile. CXCL12 fulfills its functions in homeostatic and pathological conditions by interacting with its receptors CXC chemokine receptor 4 (CXCR4) and atypical chemokine receptor 3 (ACKR3) and by binding to glycosaminoglycans (GAGs) in tissues and on the endothelium to allow a proper presentation to passing leukocytes. Homodimerizaton and heterodimerization of CXCL12 and its receptors can alter their signaling activity, as exemplified by the synergy between CXCL12 and other chemokines in leukocyte migration assays. Receptor binding may also initiate CXCL12 internalization and its subsequent removal from the environment. Furthermore, CXCL12 activity is regulated by posttranslational modifications. Proteolytic removal of NH2 - or COOH-terminal amino acids, citrullination of arginine residues by peptidyl arginine deiminases or nitration of tyrosine residues reduce CXCL12 activity. This review summarizes the interactions of CXCL12 with the cellular environment and discusses the different levels of CXCL12 activity regulation.